A STUDY OF THE VALIDITY AND RELIABILITY OF SELF-ASSESSMENT - Junaidi Mistar (TEFLIN, 2011)
Abstract: This study is to investigate whether self-assessment contains construct- irrelevant variances of gender and age, and whether self-assessment correlates with test scores. The data were collected from seventy-eight newly arrived international students at the English LanÂguage Center, Michigan State University, USA. Prior to class comÂmencement, they were asked to self-assess their listening, speaking, and interactive skill. Then, a test of listening was administered; finally, they were assigned to perform task-based conversational activities.The statistical findings imply that, firstly, gender and age do not provide construct irrelevant variances to the validity of self-assessment and, seÂcondly, self-assessment produces reliable scores.